PENYIDIKAN TINDAK PIDANA TANPA SURAT PERSETUJUAN BERLAYAR OLEH KANTOR SYAHBANDAR DAN OTORITAS PELABUHAN RENGAT BERDASARKAN UNDANG- UNDANG NOMOR 17 TAHUN 2008 TENTANG PELAYARAN - Ramadhan, Satria; Edorita, Widia (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2016)
Criminal investigations cruise by investigators civil servants (investigators) showcased in Act No. 17 of 2008 on the voyage later derivative of the regulation is the Regulation of the Minister of Transportation No. 36 of 2012 on the Organization and the Office Kesyahbandaran and the Port Authority, in the regulation that Kesyahbandaran office and Port authority (KSOP) class IV Rengat given authority to conduct patrols under field subsections sailing safety guard and patrol (KBPP). In law enforcement efforts at sea there are few records of the results of marine security and safety patrols, namely the case of vessels that have SPB, but when inspected on the high seas apparently did not have a letter of approval to sail. Not infrequently also found marine transportation accidents caused by the negligence of a harbor master to give consent and letter kelaiklautan cruise ships to ships that are not seaworthy and ships that do not pass the test.From the research there are three main issues that can be inferred. First, the role of civil servant investigators (investigators) in the Office Kesyahbandaran and Port Authority Rengat in dealing with the crime of sailing without a letter of approval to sail in the waters Rengat not optimal due to the lack of quality of Human Resources law enforcement officers (investigators) in the Office Kesyahbandaran and Port Authority Rengat , Second, Obstacle civil servant investigators (investigators) in Kesyahbandaran Office and Port Authority Rengat in criminal cases to sail without the approval letter is sailing in the waters Rengat Factor Facilities and amenities and Weak coordination among law enforcement agencies. Third, efforts made civil servant investigators (investigators) in the Office Kesyahbandaran and Port Authority Rengat against criminal cases to sail without the approval letter sail is to improve the quality of education by investigators, create a budget for the filing of a detention room Saran Writer, hoped that the Servant Investigators civil (investigators) Kesyahbandaran Office and Port Authority Rengat be maximized in handling criminal offenses sail to sail without the approval letter. As well as civil servant investigators (investigators) Kesyahbandaran Office and Port Authority Rengat can send training staff in the investigation that the investigation team can increase knowledge in conducting the investigation.Keywords: Investigation - Crime - Sailing Approval Letter